Layanan Informatif Penggunaan Media Poster Dalam Layanan Bimbingan Klasikal Untuk Peningkatan Pemahaman Kekerasan Gender Berbasis Online (Kgbo) Pada Siswa Kelas X Sma Kemala Bhayangkari 1 Kubu Raya - Dea Dwenta Septiani; Hesty Nur Rahmi; Bella Yugi Fazny (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2025)
This study aims to determine the effectiveness of informative services in improving students’ understanding of Online Gender-Based Violence through posters and lectures. A quantitative approach was applied using a quasi-experimental design of the pretest-posttest non-equivalent control group type. The subjects were tenth-grade students of SMA Kemala Bhayangkari 1 Kubu Raya, with class X B as the experimental group and class X E as the control group. Data analysis techniques included percentage analysis to measure improvement, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank test due to non-normal data. The results showed significant improvement in both groups, with posttest scores reaching 379 (85%) in the experimental group and 213 (47%) in the control group, both with a significance value of 0.000.